Review articleBiological activity selected microelements in skin and their role in diabetes - Jabłońska-Trypuć, Agata (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2007)
Like many other diseases, diabetes is associated with disorders of microelement homeostasis. Skin diseases are often involved with diabetes. Basic microelements essential for normal bodily functions are copper and zinc. They influence many metabolic and physiological processes. Both lack and excess of these elements are harmful for people. Because of skin diseases attendant in diabetes, the role of zinc and copper in metabolic processes in cuticle and stratum corneum is very important. Copper plays a very important role in melanogenesis, synthesis of collagen and in the antiradical systems. Zinc is in the structure of insulin, plays a role in taste sensation, in the antiradical systems, and participates also in regulation of levels of fatty acids and vitamin A, regulates melanogenesis, reduces the activity of 5-a-reductase, controls cell duplication and influences the immunological processes. Correct supplementation may extend the time for which there is no need to use antidiabetic drugs, while in developed diabetes it may be a great help in therapy.